2021
DOI: 10.3389/fcell.2021.611922
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial Dysfunction: Cause or Consequence of Vascular Calcification?

Abstract: Mitochondria are crucial bioenergetics powerhouses and biosynthetic hubs within cells, which can generate and sequester toxic reactive oxygen species (ROS) in response to oxidative stress. Oxidative stress-stimulated ROS production results in ATP depletion and the opening of mitochondrial permeability transition pores, leading to mitochondria dysfunction and cellular apoptosis. Mitochondrial loss of function is also a key driver in the acquisition of a senescence-associated secretory phenotype that drives sene… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
40
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(44 citation statements)
references
References 229 publications
0
40
0
1
Order By: Relevance
“…Vascular calcification was thought as senescence related degenerative damage and involved in various end-stage of chronic diseases which has got more attention in recent years. The causal relationship between calcification and mitochondria damage was still controversial [39], but mitochondrial dysfunction such as declined ATP production or decreased MMP were accompanied with vascular calcification [19,40,41]. Some studies also found mitochondria related oxidative stress damage could activate phosphatidylinositol 3-kinase/ protein kinase-B (PI3K/PKB)signaling pathway [42,43] and nuclear factor-kappa B (NF-κB) signaling pathway to promote transition of VSMCs into osteogenetic phenotype [44].…”
Section: Discussionmentioning
confidence: 99%
“…Vascular calcification was thought as senescence related degenerative damage and involved in various end-stage of chronic diseases which has got more attention in recent years. The causal relationship between calcification and mitochondria damage was still controversial [39], but mitochondrial dysfunction such as declined ATP production or decreased MMP were accompanied with vascular calcification [19,40,41]. Some studies also found mitochondria related oxidative stress damage could activate phosphatidylinositol 3-kinase/ protein kinase-B (PI3K/PKB)signaling pathway [42,43] and nuclear factor-kappa B (NF-κB) signaling pathway to promote transition of VSMCs into osteogenetic phenotype [44].…”
Section: Discussionmentioning
confidence: 99%
“…Calcified vascular cells (CVCs) perceive extracellular damage signaling and induce CVCs to differentiate into osteoblast-like cells by upregulating osteogenic factors and activating Wnt signaling, promoting vascular calcification ( Bartoli-Leonard et al, 2018 ). In chronic kidney disease, calcium and phosphorus imbalance can lead to mitochondrial dysfunction, increase the release of reactive oxygen species, trigger oxidative stress and inflammatory responses, and induce the reverse differentiation of VSMCs into osteoblast-like cells, leading to vascular calcification ( Zhu et al, 2020 ; Phadwal et al, 2021 ). At the cellular level, when the structure and function of vascular endothelial cells are abnormal, the expression of proinflammatory cytokines TNF-α and IL-1β can induce EndMT via BMP signaling, thereby inducing osteogenic differentiation and promoting vascular calcification ( Sanchez-Duffhues et al, 2019 ).…”
Section: Vascular Calcificationmentioning
confidence: 99%
“…The reduced production of ROS induces heterogeneity in cardiac action potential. Mitochondrial dysfunction reduces the mitochondrial membrane potential, further lessens ATP, and elevates ROS [ 93 ]. Subsequently, mitochondrial dysfunction is worsened concomitant with reduced mitochondrial membrane potential and ATP production.…”
Section: Mitophagy and Cardiac Diseasementioning
confidence: 99%